II.ii.74 Local Government - Labour Party (Ireland) (2006)
File containing documentation concerning two local government replacement selection conventions: in the Coole electoral area, County Westmeath, dated Jan 2006; and the Borris electoral area, County Carlow, dated Mar 2007. (22 pp)